Exhaustive diagnosis of breast implants with capsular contracture: The microbiology laboratory as a major support. Issue 9 (September 2022) - Castellano, Michele; Marín, Mercedes; Alcalá, Luis; Cunnas, Iskra; Rodríguez, Belén; Ruíz, Mª Jesús; Lasso, José; Pérez-Cano, Rosa; Bouza, Emilio; Muñoz, Patricia; Guembe, María
Summary: The most frequent complications of post-mastectomy reconstructions are breast implant (BI) infection and capsular contracture (CC). The diagnosis of BI colonization is based on cultures from the sonicated BI and from the capsule tissue. Therefore, we first aimed to assess the yield of conventional culture and molecular techniques in periprosthetic fluid, in addition to BI and capsular tissue. Moreover, we compare colonization and biofilm production between patients with and without CC. During 19 months, we prospectively included patients whose BIs had been removed and divided them into two groups: A (CC, Baker III-IV) and B (no CC). Samples were obtained for conventional culture, 16 s rRNA PCR, and MALDI-TOF. Biofilm production was also evaluated. We included 81 BIs from 69 patients with CC (22) and without CC (53). Forty-three (53.1%) of the 81 BIs had ≥1 positive culture. The culture was positive in 57.1% and 50.9% in groups A and B, respectively ( p  = 0.645). The highest 16 s rRNA PCR positivity rate was detected in capsular tissue (40.5%). MALDI-TOF was unable to detect colonization in any of the samples. High biofilm production was the following: high biomass: A, 29.8%; B, 39.7% ( p  = 0.293); high metabolic activity: A, 36.2%; B, 34.5% ( p  = 0.857). We confirm that cultures from different sites are mandatory to ensure a proper diagnosis of BI colonization. Our study is the first to demonstrate that CC was not associated with BI colonization or high biofilm production. The application of molecular techniques in BI samples was not substantially useful for predicting colonization.